Needs analysis on the development of problem based learning module for the microcontroller subject at Vocational College - Mohd Najid, Najwa; Tze Kiong, Tee; Che’ Rus, Ridzwan; Budiman, Haldi (Asian Journal of Assessment in Teaching and Learning, 2019)
Based on the analysis of student achievement throughout Vocational Colleges in Malaysia, it was found that the Microcontroller subject had the lowest achievement compared to other subjects. The results of the achievement analysis also show that students have difficulty achieving good results in the subject of Microcontroller. This indicates the need for improved implementation of the Microcontroller teaching and learning system implemented in the classroom. In regard to this matter, this study aims to identify the difficulty level of the six main topics (unit 1 - 6) and sub-topics in ETN5044 as well as the perception of the lecturers and students towards the existing module and the teaching and learning methods of the Microcontroller subject. The findings of this study shall initiate the phase of developing a learning module for the Microcontroller (ETN5044) subject using Problem Based Learning (PBL). The needs analysis also aims to determine whether the product meets the learning needs of the students. An observation was conducted involving 27 lecturers and 322 students who enroll into the 6th semester of the Electronic Technology diploma programme at several Vocational Colleges in Malaysia. The findings show that the majority of lecturers and students regard the sub-topics for topic 2 that is “Applying the instruction set of Microcontrollers” as difficult with average mean values of lecturers being 2.96, 3.07, 3.00 and 3.10, while mean values for students were 2.19, 2.21, 2.16, and 2.30. Their perception also indicates that the PBL module has never been implemented. Such findings support for the development of a learning module particularly for students undertaking the Microcontroller subject.